Does Household Finance Matter? Small Financial Errors with Large Social Costs - Bhamra, Harjoat S.; Uppal, Raman (American Economic Review, 2019)
Households with familiarity biases tilt their portfolios toward a few risky assets. The resulting mean-variance loss from portfolio underdiversification is equivalent to only a modest reduction of about 1 percent per year in a household’s portfolio return. However, once we consider also the effect of familiarity biases on the asset- allocation and intertemporal consumption-savings decisions, the welfare loss is multiplied by a factor of four. In general equilibrium, the suboptimal decisions of households distort also aggregate growth, amplifying further the overall social welfare loss. Our findings demonstrate that financial markets are not a mere sideshow to the real economy and that improving the financial decisions of households can lead to large benefits, not just for individual households, but also for society. (JEL D14, D91, E21, E44, G11, G41)